2022
DOI: 10.20338/bjmb.v16i2.272
|View full text |Cite
|
Sign up to set email alerts
|

The influence of goal-directed reaching distance on standing postural control variability in non-disabled individuals

Abstract: BACKGROUND: Performing everyday standing tasks is relevant to the individuals independence. It is a challenging postural action that requires upper extremity (UE) movements to interact with objects of the environment. Postural movement variability is a strategy of the postural system for exploring postural boundaries during the action. The distance to the target to be reached may affect the variability in postural control parameters. AIM: To test if the variability in postural control parameters is enhanced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Maintaining performance close to the participant’s limits seems to be a defining feature of this protocol [ 2 , 29 ]—an argument for its efficacy. Importantly, the possibility of maintaining this level of difficulty was only possible through the use of the RCP [ 30 ]—which is not common even in CIMT.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining performance close to the participant’s limits seems to be a defining feature of this protocol [ 2 , 29 ]—an argument for its efficacy. Importantly, the possibility of maintaining this level of difficulty was only possible through the use of the RCP [ 30 ]—which is not common even in CIMT.…”
Section: Discussionmentioning
confidence: 99%
“…That is, how practice can be manipulated to favor or hinder changes in the learner's movement possibilities. Ilha et al 13 , for instance, showed that modification of the task demands/ increase of task difficulty results in increased variability in the system -which was considered as a measure of exploration. This was demonstrated through increased variability in the center of pressure of a standing individual induced by an increase in reaching distance.…”
Section: From Basic Concepts To Candidate Viewsmentioning
confidence: 99%
“…Another interesting point was made by Profeta and Ugrinowitsch 8 in that potential theoretical disputes on what can be transferred comes from the differences from the old to the new situation. Luz, Santos and Bonuzzi 14 , Ilha et al 13 , and Anderson and Steel 16 provided interesting directions on how to optimize the process of search to, first, approximate the solution found during practice to the "maximum" potential performance referred above and, second, how to maximize retention and transfer. In this vein, ideas from Correa et al 6 (see also Profeta and Ugrinowitsch 8 ) on hierarchical systems might provide the theoretical support to understand how (and why) the discussed practice aspects (e.g., attitude, difficulty, distribution, practice schedules) when manipulated can provide better gains in motor learning.…”
Section: On the Role Of Practice In Motor Learningmentioning
confidence: 99%